Pengaruh Kesadaran Halal dan Label Halal Terhadap Minat Beli Mie Instan Korea Pada Remaja Sekolah di Jakarta - Hendradewi, Savitri; Mustika, Amalia; Darsiah, Anis (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2021)
This study aims to determine the awareness of halal and halal labels on the interest in buying Korean instant noodles in school teenagers in Jakarta. The research method used is multiple regression analysis method. The population is all school youth in Jakarta, while the sample is 100 people. Sampling by means of cluster sampling. The results showed that partially halal awareness had a significant effect on buying interest, while the halal label had no significant effect on buying interest. The greater the understanding of teenagers who love Korean instant noodles about halal, the more positive the behavior of teenagers towards things related to halal that affect buying interest. Factors that influence teenagers' buying interest in Korean instant noodles are not seen from the halal label but because the teenager really likes Korean culture from all kinds of food, clothing, music, movies, cosmetics and so on. Korean instant noodle producers are expected to continue to prioritize the halal label because teenage consumers understand their awareness to consume halal food which is important for health. Consumers can use Korean products that are halal and healthy for consumption. Keywords: Halal Awareness, Halal Label, Buying Interest